PENGARUH KEBUTUHAN AIR BERSIH TERHADAP JUMLAH PENDUDUK PULAU KARIMUN BESAR (STUDI KASUS: PDAM TIRTA KARIMUN) - Riko Rizal; Kiki Herliza (Jurnal Potensi, 2021)
The problem of providing clean water is currently a very serious problem on Karimun Besar Island. The need for clean water has increased every year while the availability of clean water is increasingly limited, due to the narrowing of infiltration areas, exploitation of raw water sources that do not pay attention to the sustainability of water sources, and the amount of reservoir discharge which is influenced by the climate on Karimun Besar Island. In order to avoid water shortages, it is necessary to maintain and preserve existing water sources, efficiency in water use and the search for new alternative sources. The purpose of this study is to analyze whether there is an effect of clean water needs on the population and to find out whether the water reservoir of the Sei Bati reservoir is in accordance with the Spatial Planning of Karimun Regency by using secondary data as reference from PDAM Tirta Karimun